SOCIO-ECONOMIC ASPECTS OF THE TRANSFORMATION OF THE LABOURMARKET AND VOCATIONAL EDUCATION TO ENSURE SUSTAINABLEDEVELOPMENT (Innovative professional education, 2024)
The section examines the current trends in the development of professional education in the countries of the European Union in view of the challenges of sustainable development of society. Political, economic, socio-demographic, and technological factors that affect professional training systems are analyzed, as well as possible threats and prospects for their development are determined. Particular attention is paid to such aspects as the unification of educational standards, the integration of ICT into the educational process, the development of entrepreneurial competence, and the adaptation of educational programs to the needs of the labor market. The implementation of the dual corporate model and its role in the vocational education system of the EU countries were also investigated.
Keywords: vocational education, sustainable development, dual corporate model, ICT, educational standards, labor market, qualification frameworks